ORAL MUCOSA LESIONS IN CHILDREN WITH SARS-COV-2 - Oana-Raluca Temneanu; Mihaela Roxana Popescu; Otilia Novac; Liliana Barbacariu; Luiza-Simona; Roxana Șerban; Bianca Simionescu; Lorena Mihaela Manole (Romanian Society of Oral Rehabilitation, 2023)
Objective: COVID-19, caused by the SARS-CoV-2 virus, has had far-reaching consequences globally, affecting people of all ages. While children generally experience mild or no symptoms, they can still be affected by the disease, in particular with oral manifestations. The understanding of oral manifestations related to COVID-19 is still limited and inconsistent. This review aims to gather and analyze data on the prevalence and clinical presentations of oral lesions in pediatric patients with SARS-CoV-2 infection, contributing to a better understanding of their relationship and classification within different forms of COVID-19. Material and Methods: A comprehensive search of medical databases was conducted to identify relevant articles published up to June 2023 searched using electronic databases such as PubMed, Medline, and Web of Science. Results: This review encompasses a systematic analysis of 33 relevant articles, with a focused examination of seven studies that specifically address the subject matter. The inclusion criteria involved thorough evaluation, with 15 articles read in their entirety and additional references searched manually for supplementary information. Discussions: Research on oral lesions in pediatric population affected by SARS-CoV-2 infection is limited, leading to potential underestimation or misdiagnosis. Oral mucosa lesions occur in 2-20% of cases, often alongside skin lesions. The most common oral lesions are erosions, ulcers, maculae, petechiae, and changes in the tongue, lips, and gingiva. Oral manifestations are also observed in Multisystem inflammatory syndrome in children (MIS-C) and Kawasaki disease associated with SARS-CoV-2. Dental care providers can play a role in identifying and monitoring MIS-C, but accurate diagnosis is crucial to prevent complications. Conclusions: Pediatric patients diagnosed with COVID-19 may not frequently exhibit recognized oral signs and symptoms, necessitating thorough evaluation and consideration of differential diagnoses. Oral healthcare professionals should assess and classify oral manifestations to prevent underestimation and misdiagnosis.